Questioni tra privati e giurisdizione militare nel IV secolo: disciplina legislativa e prassi abusiva. I casi di P. Abinn. 44-57 - Rinaudo, Alberto (Cultura giuridica e diritto vivente, 2020)
[Disputes Between Private Individuals and Military Jurisdiction in the IV Century: Legal Regulation and Illegal Practice. The Case Study of P. Abinn. 44-57] The subject confronted by this paper is the conflict between civil and military power within the jurisdictional sphere in the IV century, focusing attention, on the one hand, on the repeated interventions from the imperial legislation repressing the illegal phenomenon of petitioning military authorities in order to settle disputes between private individuals and, on the other hand, on the case study emerging from P. Abinn. 44-57, which is in contrast with the aforesaid legislation. An interesting cross-section of the complex late antique legal reality emerges, in which the authority of the law could not always prevail over the strength of an established practice.